Maternal and fetal outcome in subclinical hypothyroidism in Jammu region, North India - Singh, Gagan; Kaul, Indu; Singh, Anuradha; Meinia, Sushant Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy is a period that places great physiological stress on both the mother and the fetus in the best of times. The objective of this study was to study the maternal outcomes in terms of miscarriage, gestational hypertension, preeclampsia, placenta previa, placental abruption, preterm labour, preterm PROM, rate of caesarean section and postpartum hemorrhage. And to study the fetal outcomes in terms of premature birth, low-birth weight, fetal distress in labour, fetal death and congenital anomalies. Methods: The studied subjects included all pregnant women reporting to the hospital for a period of one year November 2012 to October 2013. All participants were subjected to detailed history, thorough general physical, systemic, local examinations, and routine investigations, thyroid function tests (serum TSH, T3, T4). All participants were divided into two groups, group-I: pregnant women diagnosed with subclinical hypothyroidism (TSH 5-10Mu/L; T3 and T4 normal), group-II: euthyroid pregnant women (control group). Maternal and fetal outcomes of subjects in the first group (study) were compared with control group. The data was analyzed using computer software Microsoft Excel and SPSS version 19.0 for Windows. Chi square test was performed to evaluate statistical significance. A p-value of <0.05 was considered as statistically significant. Results: A total of 17045 pregnant women reported to labour room and OPD and 15120 women qualified after applying exclusion criteria. Out of these, 14770 pregnant women were found euthyroid and subclinical hypothyroidism was identified in 350 (2.05%) women. Maternal outcome in study group in terms of miscarriage (p<0.001), gestational hypertension (p<0.001), placental abruption (p<0.0001) and preterm premature rupture of membrane (p=0.007) was found to be statistically significant when compared with control group, while fetal outcome in terms of fetal distress (p<0.001), low birth weight (p<0.001) and premature birth (p=0.002) was found to be statistically significant. Conclusions: In view of adverse maternal and fetal outcome, detecting and treating the women with subclinical hypothyroidism in early pregnancy will improve the perinatal outcome.